LEVERAGING DIGITAL OPPORTUNITY IN THE CULINARY SECTOR: A CASE STUDY OF SEBLAK PRASMANAN'S COMPETITIVE STRATEGY THROUGH SWOT-TOWS ANALYSIS IN LHOKSEUMAWE, ACEH. - Miftahul Jannah; Nur Afni; Rauzi Ramazalena; Nova Rianti S (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the competitiveness of Seblak Prasmanan, a micro culinary enterprise in Lhokseumawe Aceh, using the SWOT and TOWS Matrix approaches. The SWOT analysis identifies key strengths, including the unique buffet-style concept, consistent product quality, and a loyal local customer base. However, notable weaknesses are limited digital marketing capacity, the absence of professional financial management, and high dependence on the local market. Externally, opportunities arise from the rapid growth of digital platforms, government support for MSME digitalization, and the enduring appeal of traditional culinary culture. Conversely, threats include intense competition, shifting consumer preferences, and economic fluctuations affecting input costs and profit margins. The TOWS Matrix develops four strategic alternatives. The SO strategies recommend leveraging product uniqueness to expand into digital markets through collaboration with food delivery platforms and targeted social media campaigns. The WO strategies highlight internal capacity building through digital training and government assistance. The ST strategies focus on product differentiation and loyalty programs to mitigate competition. Meanwhile, the WT strategies adopt a defensive approach emphasizing operational efficiency and gradual adoption of digital tools. This study underscores the importance of balancing the preservation of local culinary authenticity with the adoption of digital strategies to enhance competitiveness. The findings contribute to the literature on MSME strategic management by providing empirical evidence on the application of the SWOT–TOWS framework in the context of traditional food businesses in emerging markets.